PERAN PEMERINTAH DALAM PENGEMBANGAN KOMPETENSI PELAKU UMKM DI KECAMATAN GALESONG SELATAN KABUPATEN TAKALAR - Ismail, Muhammad Ilham; Marhumi, Sitti; Akib, Muhammad (LPPM - STIE SAKTI ALAM KERINCI, 2025)
The purpose of this study is to determine the Role of Government in Developing the Competence of SME sectors in Galesong Selatan District, Takalar Regency. This type of research is descriptive research with a qualitative approach. The data processed are the results of interviews conducted with 5 informants, namely the Head of Government, Head of Economics, Wholesale Figures, Craftsmen, Street Vendors. The data collection methods used in this study are observation, interviews and documentation.The results of the study are that the Government plays an active role in developing the competence of SME sectors in South Galesong District through product innovation training, development of SME (small medium enterprise) training. This program aims to improve skills, competitiveness, and marketing of local products, so that MSMEs can contribute more to the regional economy.